Systematic review with meta‐analysis: recurrence of Crohn's disease after total colectomy with permanent ileostomy. Issue 3 (8th December 2016) - Fumery, M.; Dulai, P. S.; Meirick, P.; Farrell, A. M.; Ramamoorthy, S.; Sandborn, W. J.; Singh, S.
Summary: Background: Subtotal or total colectomy or proctocolectomy with permanent ileostomy (TC‐PI) may be a treatment option for medically refractory colonic Crohn's disease (CD). Aim: To perform a systematic review and meta‐analysis to evaluate the rate, risk factors and outcomes of CD recurrence after TC‐PI. Methods: In a systematic review ending 31 March 2016, we identified 18 cohort studies (1438 adults) who underwent TC‐PI for colonic CD (median follow‐up, 7.4 years; interquartile range, 5.3–9.0). We estimated pooled rates [with 95% confidence interval (CI)] of clinical and surgical recurrence, and risk factors for disease recurrence. Results: On meta‐analysis, the risk of clinical recurrence after TC‐PI was 28.0% (95% CI, 21.7–35.3; 14 studies, 260/1004 patients), with a 5 and 10‐year median cumulative rate of 23.5% (range, 7–35) and 40% (range, 11–60) respectively. The risk of surgical recurrence was 16.0% (95% CI, 11.1–22.7; 10 studies; 183/1092 patients), with a 5 and 10‐year median cumulative rate of 10% (range, 3–29) and 18.5% (range, 14–34) respectively. The risk of clinical and surgical recurrence in patients without ileal disease at baseline was 11.5% (95% CI, 7.7–16.8) and 10.4% (95% CI, 4.5–22.5) respectively. History of ileal disease was associated with 3.2 times higher risk of disease recurrence (RR, 3.2; 95% CI, 1.8–5.6). Other inconsistent risk factors for disease recurrence were penetrating disease and young age at disease onset. Conclusions: Small bowel clinical recurrence occurs in about 28% of patients after total colectomy with permanent ileostomy for colonic Crohn's disease. Disease recurrence risk is 3.2 times higher in patients with history of ileal disease, and continued medical therapy may be advisable in this population. In patients without ileal inflammation at surgery, continued endoscopic surveillance may identify asymptomatic disease recurrence to guide therapy. Abstract : Linked Content This article is linked to Yamamoto and Shimoyama paper. To view this article visithttps://doi.org/10.1111/apt.13946 .